Aeolothrips neyrizi, a new species of the genus Aeolothrips (Thysanoptera: Aeolothripidae) from southern Iran - Minaei, Kambiz; Alavi, Jalil (Zootaxa, 2017)
Aeolothrips neyrizi n. sp. is described and illustrated from Fars province, southern Iran, on the basis of two females collected from Alhagi persarum (Fabaceae). The fore wing colour is characteristic of the species. The new species is closely related to A. afghanus, a species that has been described from Afghanistan and also reported from Iran.